Pertimbangan Investor dalam Berinvestasi Berdasarkan Day of The Week Effect dan Turn of Month Effect - Batara Daniel Bagana; Arief Himmawan D.N (Jurnal Bisnis dan Ekonomi, 2018)
Seasonal anomaly occurring in the capital market through time mainly occurs through the phenomenon of Day of the Week Effect and Turn of Month Effect. The research examining the effect of the Day of the Week Effect on the Indonesia Stock Exchange (IDX) has been done quite a lot, but there has been no inclusion of the Turn of Month Effect element in his research. Most researchers also use a limited period in their research. This article examines the Effects of Day of the Week and Turn of Month Effect that occur in the Indonesia Stock Exchange and uses a long data period. This study uses the daily return of the Composite Stock Price Index (IHSG) starting July 1, 2000 until June 3, 2017. The analysis was carried out using the GARCH method. All days used in trading have a significant impact on the return of the JCI. The trading days outside Monday have a positive and significant influence on the JCI. The days of the Turn of Month Effect have a positive and significant effect on the yields of the Composite Stock Price Index.